The determination of pH of peri‐implant crevicular fluid around one‐piece and two‐piece dental implants: A pilot study - Karpavicius, Dainius (Clin Exp Dent Res, 2019)
There are two main groups of screw‐type dental implant designs: one‐piece and two‐piece implants. Although success rates of both of these types of implants are high, none of them avoid complications, of which the most common are peri‐implant mucositis and peri‐implantitis. Current clinical diagnostic parameters are relatively noninvasive and cost‐efficient; however, they are often not sensitive enough and fail to determine the activity of inflammation. The purpose of this study is to determine pH of peri‐implant crevicular fluid (PICF) around one‐piece and two‐piece implants and pH of gingival crevicular fluid (GCF) around healthy teeth and to find out if our suggested method could function accurately for determination of pH of PICF and GCF. Thermo Fisher Scientific™ Orion™ 9863BN glass microelectrode was used to determine pH of PICF around 29 one‐piece (ROOTT, TRATE AG) and 29 two‐piece implants (multiple manufacturers) and pH of GCF around 29 healthy teeth. pH of PICF around two‐piece implants was more acidic (P < 0.001). Average pH around one‐piece implants was 6.46 and around two‐piece implants was 6.15. Mean pH of GCF was 6.64. pH of PICF in women around two‐piece implants was more alkaline (P < 0.05); no difference was found in control and one‐piece implant groups. There was no statistically significant correlation found between age and pH of PICF and GFC. Design of dental implants has an impact on pH of PICF. Glass microelectrode is an appropriate tool for accurate determination of pH in PICF.